Arbitrase ditinjau dari Reglemen Acara Perdata(Rv), Peraturan Prosedur BANI, International Centre for the Settlement of Investmen Disputes(ICSID), UNCITRAL Arbitration Rules, Convention on the Recognition and Enforcement of Foreing Arbitral Award, PERMA N - M. Yahya Harahap (Sinar Grafika, 2006)
...C.1-4